Overdominant effect of a CHRNA4 polymorphism on cingulo-opercular network activity and cognitive control - Sapaghiani, Sepideh; Banaschewski, Tobias; Flor, Herta; Nees, Frauke (The journal of neuroscience, 2017)
The nicotinic system plays an important role in cognitive control, and is implicated in several neuropsychiatric conditions. Yet, the contributions of genetic variability in this system to individuals' cognitive control abilities are poorly understood, and the brain processes that mediate such genetic contributions remain largely unidentified. In this first large-scale neuroimaging genetics study of the human nicotinic receptor system (two cohorts, males and females, fMRI total N=1586, behavioral total N=3650), we investigated a common polymorphism of the high-affinity nicotinic receptor α4β2 (rs1044396 on the CHRNA4 gene) previously implicated in behavioral and nicotine-related studies (albeit with inconsistent major/minor allele impacts). Based on our prior neuroimaging findings, we expected this polymorphism to impact neural activity in the cingulo-opercular network involved in core cognitive control processes including maintenance of alertness. Consistent across the cohorts, all cortical areas of the cingulo-opercular network showed higher activity in heterozygotes compared to both types of homozygotes during cognitive engagement. This inverted U-shaped relation reflects an overdominant effect, i.e. allelic interaction (cumulative evidence p=1.33*10-5). Furthermore, heterozygotes performed more accurately in behavioral tasks that primarily depend on sustained alertness. No effects were observed for haplotypes of the surrounding CHRNA4 region, supporting a true overdominant effect at rs1044396. As a possible mechanism, we observed that this polymorphism is an expression quantitative trait locus (eQTL) modulating CHRNA4 expression levels. This is the first report of overdominance in the nicotinic system. These findings connect CHRNA4 genotype, cingulo-opercular network activation and sustained alertness, providing insights into how genetics shapes individuals' cognitive control abilities. Significance Statement: The nicotinic acetylcholine system plays a central role in neuromodulatory regulation of cognitive control processes, and is dysregulated in several neuropsychiatric disorders. In spite of this functional importance, no large-scale neuroimaging genetics studies have targeted the contributions of genetic variability in this system to human brain activity. Here, we show impact of a common polymorphism of the high-affinity nicotinic receptor α4β2, consistent across brain activity and behavior in two large human cohorts. We report a hitherto unknown overdominant effect (allelic interaction) at this locus, where the heterozygotes show higher activity in the cingulo-opercular network underlying alertness maintenance, and higher behavioral alertness performance than both homozygous groups. This gene-brain-behavior relationship informs about the biological basis of inter-individual differences in cognitive control.
Published online: 6 September 2017
Gesehen am 06.06.2018